A Contemporary Overview about Status and Challenging Issues of Tribal Education in India - V. Rajkumar Velusamy (International Journal of Asian Education, 2021)
India is the second-largest tribal population in the world. However, after the seven decades of independence, the tribal groups are disadvantaged and socially backward from the cycle of growth in many areas such as health, education, employment, and empowerment, and more. Among these, for tribal society, education is an essential requirement. The state and central governments have initiated several programs to educate tribal groups. Many of these programs have achieved only 10 percent of the targets. The vast numbers of tribal peoples are missing their education at various levels. They lag in education due to the high illiteracy rates among the tribal population relative to Scheduled Castes (S.C.s). Hence, the time has come to consider tribal education and inclusive growth seriously. In this context, the comprehensive literature review seeks to provide a contemporary overview of India's current status and challenging issues of tribal education. The paper is purely based on second-hand information from various research studies conducted in India and collected from different government sources. The outcomes are more helpful in implementing schemes that can improve tribal literacy and inclusive growth perspectives.